Presentation of the Center for the Study of New Testament Manuscripts: Bridging the Gap between Ancient Manuscripts and Modern Technology - Ladewig, Stratton L. (Open theology, 2019)
This article seeks to expound upon the first facet of CSNTM’s mission: to capture firsthand digital images of Greek New Testament manuscripts with high resolution digital equipment. By cooperating with likeminded libraries, CSNTM accomplishes the preservation and presentation of cultural heritage artifacts via the utilization of the advances of technology. Details of collaboration, digitization procedures, and preservation and presentation practices are explored, providing a glimpse into this world of artifact digitization. The article then turns to the consideration of ways to improve both digitization and the end user’s experience. While CSNTM engages libraries, archivists, researchers, and students, supportive partners serve to facilitate the work. All are essential, enabling CSNTM to preserve and provide access to timeless treasures.